2022
DOI: 10.1038/s41598-022-17060-y
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of stacking fault expansion in a 4H-SiC epitaxial layer by proton irradiation

Abstract: SiC bipolar degradation, which is caused by stacking fault expansion from basal plane dislocations in a SiC epitaxial layer or near the interface between the epitaxial layer and the substrate, is one of the critical problems inhibiting widespread usage of high-voltage SiC bipolar devices. In the present study, we investigated the stacking fault expansion behavior under UV illumination in a 4H-SiC epitaxial layer subjected to proton irradiation. X-ray topography observations revealed that proton irradiation sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The reduction in carrier lifetime also influences the suppression of expansion, and proton implantation reduces carrier lifetime 32 , 36 . We observed carrier lifetimes in a 60 µm-thick epitaxial layer with 10 14 cm −2 proton implantation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in carrier lifetime also influences the suppression of expansion, and proton implantation reduces carrier lifetime 32 , 36 . We observed carrier lifetimes in a 60 µm-thick epitaxial layer with 10 14 cm −2 proton implantation.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in the case of the lightest element, hydrogen, an ion (proton) can be implanted at a depth of more than 10 µm in 4H-SiC using a MeV-class accelerator. Therefore, if proton implantation affects the pinning of PDs, then it can be used to suppress the expansion of BPDs in the substrates 36 . However, proton implantation can damage 4H-SiC and result in the deterioration of device performance 37 40 .…”
Section: Introductionmentioning
confidence: 99%
“…35,36) Recently, we have reported that proton irradiation, which is commonly used in semiconductor processing, can suppress SF expansion in the SiC epitaxial layer driven by ultraviolet (UV) illumination and forward bias application. 21,37) Although we carefully separated the effect of change in carrier lifetimes on the driving force of SF expansion and the effect of the pinning of dislocations by proton implantation, the relationship between dislocation mobility and proton implantation has remained unclear. In the present study, we investigated the contraction behavior of SFs subjected to proton implantation and revealed the relationship between dislocation mobility and proton implantation.…”
mentioning
confidence: 99%
“…The detailed hydrogen density profile is shown in Ref. 37. After the proton implantation, the specimens were heated to 873 K in a nitrogen atmosphere for 10 min.…”
mentioning
confidence: 99%
See 1 more Smart Citation